1996
DOI: 10.1152/ajpregu.1996.270.3.r660
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pioglitazone on vascular reactivity in vivo and in vitro

Abstract: Pioglitazone (a thiazolidinedione derivative) increases insulin sensitivity and prevents hypertension in the Dahl-salt-sensitive (S) rat. The present study was undertaken to determine if pioglitazone modulates pressor responsiveness to vasoactive agents, both in vivo and in vitro. In vivo, pretreatment with pioglitazone inhibited (P < 0.02) pressor responses to both norepinephrine and angiotensin II in conscious Dahl-S, but not in Sprague-Dawley rats. In vitro, pioglitazone augmented the capacity of insulin to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 0 publications
3
27
1
Order By: Relevance
“…Therefore, it is suggested that pioglitazone exerts its antihypertensive effect by improving insulin sensitivity and also by another mechanism. In recent studies, pioglitazone showed a direct effect on vascular smooth muscle cells to inhibit calcium ion influx, resulting in the inhibition of blood vessel constriction and vascular cell growth and decreasing the blood pressure (27)(28)(29). In this study, however, the improvement of insulin resist ance rather than the direct effect of pioglitazone on arterial cells seems to contribute much to the blood pressure reduction.…”
Section: Discussioncontrasting
confidence: 51%
“…Therefore, it is suggested that pioglitazone exerts its antihypertensive effect by improving insulin sensitivity and also by another mechanism. In recent studies, pioglitazone showed a direct effect on vascular smooth muscle cells to inhibit calcium ion influx, resulting in the inhibition of blood vessel constriction and vascular cell growth and decreasing the blood pressure (27)(28)(29). In this study, however, the improvement of insulin resist ance rather than the direct effect of pioglitazone on arterial cells seems to contribute much to the blood pressure reduction.…”
Section: Discussioncontrasting
confidence: 51%
“…1,4 Accumulating evidence indicates that rosiglitazone also possesses potent blood pressure-lowering effects in patients or animal models of both diabetes mellitus/metabolic and nondiabetes/metabolic syndrome, [7][8][9][10][11] although the underlying mechanisms are not fully elucidated. All hitherto implicated mechanisms, including the ability to inhibit the proliferation of arterial smooth muscle cells, 29 prevent augmented vasoconstriction to vasoactive compounds, 30 protect endothelialdependent vasodilation, 31 or increase in NO production/ availability, 32 depict peripheral effects of rosiglitazone. However, controversy still exists on the role of PPAR-␥ in vascular smooth muscle cells and endothelial cells in hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…26 Thiazolidinediones are also associated with nonglycemic metabolic benefits, including favorable changes in lipids. 12,13,27 Thiazolidinedione treatment is associated with modest blood pressure lowering, 21,28 reduced carotid intimamedia thickness, 29 antiinflammatory effects, 30 and enhanced fibrinolysis, 31 endothelial function, 32 and left ventricular remodeling after myocardial infarction in animal models. 33 These effects provide potential mechanisms to account for lower mortality with thiazolidinedione treatment in this highrisk older population with heart failure.…”
Section: Masoudi Et Al Insulin Sensitizers and Heart Failure Outcomesmentioning
confidence: 99%